Experiences and beliefs of Malawian women who have delivered with a traditional birth attendant. Issue 1 (6th January 2015) - Ryan, Julia; Hamela, Gloria; Chome, Nelecy; Kabondo, Charity; Hosseinipour, Mina; Tang, Jennifer
Abstract: Objective: To explore the beliefs and experiences of Malawian women who have delivered with a traditional birth attendant (TBA). Methods: In a qualitative study, 20 face‐to‐face in‐depth interviews and three focus group discussions were conducted between February and May 2013. Women aged 18 years or older and who had a history of delivery with a TBA were recruited from three health centers in Lilongwe District. Their responses were independently coded, and content analysis was used to develop themes and subthemes. Results: A total of 46 women participated. Most participants cited difficulties relating to transport and/or unsupportive or unavailable husbands as factors that prohibited their delivery at a health facility. Most had not had a specific delivery plan. The participant responses indicated a discordance between knowledge and practices for safe delivery. Conclusion: Strategies to decrease deliveries with TBAs should focus on helping women to develop delivery plans to cope with the potential social or situational obstacles of getting to a facility. Women desire health facilities that provide quality care, emotional support, and personalized care during labor and delivery.